Nafkah Iddah Pasca Perceraian Perspektif Hadis: (Studi Kasus di Desa Panaguan Kecamatan Larangan Kabupaten Pamekasan) - Sulalah, Anis; Putri Alfia Halida (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2023)
If the divorce is granted by the court, it will have consequences as contained in Islamic Law Compilation (149), one of which is regarding the obligation to provide. However, in reality, the community thinks that the obligations at home also end, resulting in the rights of the wife not being fulfilled, as happened in the people of Panaguan village. This article aims to explain the factors causing the fulfillment of iddah income after divorce as well as a review of hadiths regarding the obligations of post-divorce maintennace of iddah. This research includes empirical or field research with a case study approach using qualitative research methods. Primary data sources were obtained through interviews, while secondary data was sourced from literature review. Research result are; (1) Implementation of post-divorce iddah maintenance in Panaguan village was not realized properly because many ex-wives did not get the right to iddah maintenance due to a lack of knowledge of the religious community regarding post-divorce living, lack of legal understanding of post-divorce rights, intentional factors, divorce out of court, as well as community customs. (2) In reviewing the hadiths, the obligation to support iddah has previously been regulated in the Qur’an in QS. at-Thalaq verse 6 and reinforced by a hadith narrated by an-Nasa’i in the book of Sunan al-Nasa’i. Additionally, QS. al-Baqarah verse 241 is reinforced in by hadith narrated by Ibn Majah in the book Bulg al-Marm min Adillatil Ahkm and is found in the hadith narrated by Muslim as well as in the same book.